Raising readers : how to nurture a child's love of books - Daley, Megan (University of Queensland Press, 2019)
An essential and practical resource for parents and educators, Raising Readers contains everything you need to know about childhood literacy, written by award-winning teacher librarian Megan Daley. Some kids refuse to read, others won't stop - not even at the dinner table! Either way, many parents question the best way to support their child's literacy journey. When can you start reading to your child? How do you find that special book to inspire a reluctant reader? How can you tell if a book is age appropriate? What can you do to keep your tween reading into their adolescent years? Award-winning teacher librarian Megan Daley has the answers to all these questions and more. She unpacks her fifteen years of experience into this personable and accessible guide, enhanced with up-to-date research and first-hand accounts from well-known Australian children's authors. It also contains practical tips, such as suggested reading lists and instructions on how to run book-themed activities. Raising Readers is a must-have guide for parents and educators to help the children in their lives fall in love with books.